(untitled) (Jurnal Destinasi Pariwisata, 2025)
This research focuses on the development of the Colol Tourism Village after it was designated as a tourist village. This research uses qualitative research. Tourism development in East Manggarai Regency applies the concept of community-based tourism. The basic principle in developing tourism with the CBT concept is to place the community as the main actor in every tourism activity with the aim of improving community welfare. In developing a tourist village, community involvement is a very important element. Community involvement in the tourism development process in the village is also usually called "participation". Participation means voluntarily involving people or groups in an activity. Because community participation for the sustainability of tourism in the village has a big influence on the development of the tourist village. The community, as a direct actor in preparing all tourism potential in the village, will later act as a host for visiting tourists. So, with community participation in the development of tourist villages, it is hoped that it can influence various aspects in the village such as the livelihood of the population, changes in social structure, changes in leadership roles, cultural changes, and changes in the level of welfare of the village community. The main problem in this research is that the involvement of local communities in Colol Tourism Village is still lacking. So that the tourism life cycle is identified in the Colol Tourist Village, it is found the Colol Tourist Village is still in the involvement stage. Meanwhile, community involvement is still on a small scale such as participating in government programs such as training and socialization